Iowa RBA, December 30, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for December 23, 1996. Highlights of the update include sightings of a Clark's Nutcracker, a Pinyon Jay, a Varied Thrush, an Evening Grosbeak, and a Snowy Owl. Other interesting observations were of a male Evening Grosbeak, a Snowy Owl, and two Red-shouldered Hawks. Also included are handwritten notes for the next week's update with sightings of a Spotted Towhee and a first year Mew Gull. Epson - sheet feed/flatbed